35. KNOWLEDGE, ATTITUDES, AND PRACTICES TO ENSURE SAFETY FOR CHILDREN UNDER 6 YEARS OLD AS MOTORBIKE PASSENGERS AT VIET TRIEU KINDERGARTEN, DONG DA DISTRICT, HANOI IN 2023 (Vietnam Journal of Community Medicine, 2024)
Introduction: Describe the knowledge, attitude and practice on road traffic safety of motorcycle transportation for children under 6 in the Viet Trieu kindergarten, Dong Da district, Hanoi 2023. Methods: Cross-sectional study using quantitative interview method was conducted, with a total of 267 cases of adults carrying children as passengers on a motorbike. Results: The research results showed that the proportion of people who have knowledge and positive attitudes towards children transportation on motorbike was respectively 77.9% and 85.4%, and the proportion of people who use at least one safety device for children, safely let children get on and off the motorbike, do not exceed the maximum number of children allowed as passengers, and do not let children sit in front of the driver was 45.3%. In terms of knowledge, 77.9% of the adult drivers with children passengers had good knowledge of the laws and regulations related to child safety, appropriate behaviors to ensure child safety, and knowledge of traffic accidents with children passengers. In terms of attitude, only 14.6% of the participants had a negative attitude when being asked about the potential risks of having children as motorbike passengers. Conclusion: Over 50% had a positive attitude towards ensuring child safety.
Keywords: Child safety, motorbike, helmet, child seat for motorbike, safely getting on and off the motorbike.